POST-MORTEM LESIONS of UROLITHIASIS IN A LESSER SEED FINCH (Sporophila angolensis). - Marietto-Goncalves, Guilherme Augusto; Salgado, Breno Sousa (My University, 2012)
Urolithiasis is a disease that despite being a commonly observed problem in veterinary practice is uncommon in birds. Such disease was not reported in passeriforms to date. Accordingly, the aim of the present article is to describe a case of urolithiasis in an adult female lesser seed finch (Sporophila angolensis) pet bird which presented abdominal distension, respiratory distress, and apathy prior to death. The bird had history of being fed with a diet rich in protein. After the bird death, a necropsy was conducted in order to determine the cause of death. At necropsy, accentuated ascites, hydropericardium, and ureteral stones in the left ureter could be grossly observed. Additional tests related with viral and bacterial microbiological testing and with the determination of calculi composition could not be performed since the owner did not consent with the procedures because of the cost. Since the bird was fed on a high protein diet, a relationship between the ureteroliths and dietary imbalance was suggested with participation of protein in calculi development by providing the organic nuclei. Additionally, we conclude that the presence of calculi in the ureter resulted in urinary flow blockage, ascites, and consequent acute respiratory failure due to filling of air sacs with liquid.